Dari Motif Kawung ke Algoritma Visual: Sebuah Pendekatan dalam Pembelajaran Komputasi untuk Desainer - Nurrachman, Muhammad Irfan (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
This research explores the potential of the kawung motif as an innovative algorithmic learning medium for designers. By analyzing in depth the geometric elements that make up the kawung motif, this research succeeded in identifying the underlying algorithmic principles. The research results show that the kawung motif can be deconstructed into a series of simple computational steps and described in the form of a visual algorithm, so it can be an effective tool for teaching basic programming concepts for designers. This approach not only increases designers' understanding of abstract mathematical concepts and algorithmic thinking, but also fosters appreciation for the nation's cultural heritage. Thus, this research makes a significant contribution to developing a learning curriculum that is relevant to the demands of the 21st century, while preserving the nation's cultural values.